Avaliaç\~ao de licitaç\~oes e proposiç\~ao de alternativas para o transporte intermunicipal de passageiros por ônibus - George Vasconcelos Goes; Erivelton Pires Guedes; Fabiano Mezadre Pompermayer (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– This study conducts an evaluation of the tender for intercity passenger transport by bus in selected states of Brazil with the purpose of carrying out a preliminary diagnosis and pointing out alternatives in the light of good public transport management practices. For this, bidding processes in selected states are reviewed, as well as supply and demand data are modeled, as well as the attractiveness, in terms of competition, of current systems, showing that it is possible to modernize and make the system more flexible and attract more competitors, even within the concession regime. The study highlights the need to review the criteria that establish the period of operation of the service and the methods for reviewing and readjusting the fare in public transport operating regimes. The regulation of road agencies is also recommended for the improvement of the regulation of the public service, as well as the computerization and unification of the databases of the granting power and concessionaires. Furthermore, low-cost operational measures such as Global Positioning System (GPS) tracking, electronic billing, user information system and risk matrices, together with performance evaluation indicators, would provide the primary data needed to plan and monitor the system. Finally, the implementation of a user information system would allow greater visibility of the bus offer, which could increase the reliability of the system's travel time and, therefore, also the demand.
10419/284919
Keywords: K23; L92; R41; 330; intercity transportation; bidding; regulated industry